A survey-based case study to assess the computer skills of incoming first-year students in Translation and Interpreting - Plaza-Lara, Cristina (Peter Lang, 2022)
In Translation Studies, the translator’s instrumental competence, directly related to computer knowledge, has gained significant importance and computer- assisted translation or localisation skills are nowadays essential to access the labour market. In order to teach students to use these specific technologies in the translation field, it is necessary that they have in advance a solid base of computer skills. For this reason, this paper presents a survey- based case study that aims to shed light on the level of computer knowledge that incoming first- year students have when they start their studies in Translation and Interpreting. The research has been carried out in a Spanish university and the aim is to confirm whether the group of students that took part in the study had previously developed the technological skills needed to start developing the translator’s instrumental competence. Although the study only focuses on a Spanish academic institution and conclusions cannot be extrapolated to other scenarios until further research is carried out, according to the results provided by the group, it has been concluded that, in spite of the fact that students cannot be considered illiterate with regard to their use of new technologies, their general computer skills should be reinforced during the degree before they are introduced to the use of more specialised translation tools.
Keywords: Innovaciones tecnológicas; Aptitud; Traducción - Estudio y enseñanza superior - Estudio de casos; Instrumental competence; Incoming first-year students; Translation training; New technologies; Survey-based case study